Assisting im3 Partners in Developing Micro and Small Enterprises - Santoso; Zaenal Abidin; Kurniawan; Fitri Nurdianingsih; H Ahmad (Zabags International Journal of Engagement, 2025)
Micro and small enterprises (MSEs) play a strategic role in local economic development, yet they continue to face challenges in market access, digital literacy, and managerial effectiveness. This study aims to explore the technical assistance provided by university students to IM3 business partners in enhancing product management, digital marketing strategies, and distribution systems in the Talang Babat region. Employing a qualitative approach with a phenomenological strategy, the research draws on primary data from participatory observation, in-depth interviews, and documentation of Field Experience Practice activities. The findings reveal that collaborative engagement between academia and industry significantly improves partners’ understanding of telecommunications products, strengthens social media-based promotional strategies, and optimizes inventory tracking and product distribution. The interaction among students, business partners, and service providers fosters a productive synergy in building a local business ecosystem responsive to communication technologies. This study contributes to the development of a replicable MSE assistance model grounded in the Triple Helix framework and phenomenological inquiry, offering practical implications for educational institutions, industry stakeholders, and policymakers in designing more contextual and sustainable MSE empowerment strategies.